2020
DOI: 10.1002/ange.202001523
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative Assembly of Macrocycles Comprising Multiple Transient Bonds

Abstract: Dissipative assembly has great potential for the creation of new adaptive chemical systems.H owever,w hile molecular assembly at equilibrium is routinely used to prepare complex architectures from polyfunctional monomers,species formed out of equilibrium have,tothis point, been structurally very simple.I nm ost examples the fuel simply effects the formation of as ingle short-lived covalent bond. Herein, we show that chemical fuels can assemble bifunctional components into macrocycles containing multiple transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…The majority of the studies reported so far are related to non‐covalent dissipative self‐assembly of activated synthetic compounds, resulting in transient supramolecular structures with properties and life‐times that can be tuned by the kinetics of fuel conversion [3,4,6,15,16] . Examples of transient functional materials are structures capable of self‐correction, [17] product selection, [18] helical conformational switching, [19] transport of molecular cargo, [20,21] and molecular hosts [22] . Cyclic reaction networks have also been designed where the activated state functions as a catalyst for a chemical reaction, whereas the deactivated state is inactive.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the studies reported so far are related to non‐covalent dissipative self‐assembly of activated synthetic compounds, resulting in transient supramolecular structures with properties and life‐times that can be tuned by the kinetics of fuel conversion [3,4,6,15,16] . Examples of transient functional materials are structures capable of self‐correction, [17] product selection, [18] helical conformational switching, [19] transport of molecular cargo, [20,21] and molecular hosts [22] . Cyclic reaction networks have also been designed where the activated state functions as a catalyst for a chemical reaction, whereas the deactivated state is inactive.…”
Section: Introductionmentioning
confidence: 99%
“…1,[15][16][17] Carbodiimides, typically EDC ((N -(3-(dimethylamino)-propyl)-N -ethylcarbodiimide hydrochloride), stand out as versatile fuels. They have been used in recent reports by Boekhoven, [18][19][20] us, [21][22][23] Das, 24,25 and several other research groups [26][27][28] to generate nonequilibrium behavior. The associated chemistry is quite simple: carbodiimides react with aqueous carboxylic acids to generate carboxylic anhydrides that then undergo hydrolysis to regenerate the parent carboxylic acids.…”
Section: Introductionmentioning
confidence: 99%